Relationship between Chronotype and Stress Level in Female Students during COVID-19 Pandemic - Lestari, Puji; Pamungkasari, Eti Poncorini; Andayani, Tri Rejeki (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: The Corona Virus Disease (COVID-19) pandemic has a negative impact on all sectors of life, especially in adolescence.The quality of sleep of that the impact and it can increase stress level. Objective: This study aims to analyze the relationship between chronotype and stress levels in female students during the Covid-19 pandemic. Materials and Methods: This is observational study with a cross-sectional design used the Morningness- Eveningness Questionnaire (MEQ) and Perceived Stress Scale (PSS-10) in 171 female students as respondents. The data were statistically analyzed using Rank Spearman test. Results: The results showed that 46,2% of respondents had intermediate chronotype and 7,6% evening chronotype. There are 81,3% of respondents with moderate stress and 9,9% of respondents with high perceived stress. There is relationship between chronotype and stress level in female students (p=0,000, r= 0,286). Conclusion: There is relationship between chronotype and stress level in female students during COVID-19 pandemic. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 438-441